TUBERCULOSIS IN CHILDREN - Susanna Esposito (Mediterranean Journal of Hematology and Infectious Diseases)
Tuberculosis (TB) in children is a neglected aspect of the TB epidemic despite it constituting 20% or more of all TB cases in many countries with high TB incidence. Childhood TB is a direct consequence of adult TB but remains overshadowed by adult TB because it is usually smear-negative. Infants and young children are more likely to develop life-threatening forms of TB than older children and adults due to their immature immune systems. Therefore, prompt diagnoses are extremely important although difficult since clinical and radiological signs of TB can be non-specific and variable in children. Despite undeniable advances in identifying definite, probable, or possible TB markers, pediatricians still face many problems when diagnosing TB diagnosis. Moreover, curing TB can be difficult when treatment is delayed and when multi-drug resistant (MDR) pathogens are the cause of the disease. In these cases, the prognosis in children is particularly poor because MDR-TB treatment and treatment duration remain unclear. New studies of diagnostic tests and optimal treatment in children are urgently needed with the final goal of developing an effective anti-TB vaccine.